Prevalence of alpha-papillomavirus genotypes in cervical squamous intraepithelial lesions and invasive cervical carcinoma in the Italian population - Tornesello, Maria Lina; Duraturo, Maria Luisa; Botti, Gerardo; Greggi, Stefano; Piccoli, Roberto; De Palo, Giuseppe; Montella, Maurizio; Buonaguro, Luigi; Buonaguro, Franco M. (Journal of medical virology, 2006)
The aim of the present investigation was to define the spectrum of mucosotropic human papillomaviruses among 414 Italian women with normal cervices (n = 183), low‐ and high‐grade cervical squamous intraepithelial lesions (n = 101 and 65, respectively), and invasive squamous cervical carcinomas (n = 65). Human papillomaviruses were detected by broad spectrum consensus‐primer‐pairs MY09/MY11 and GP5+/GP6+‐based polymerase chain reaction using three amplification methods and were characterized by nucleotide sequence analysis. The prevalence rates of HPV infections was 19.7%, 63.4%, 80%, and 81.5% in patients with normal cervices, low‐grade, and high‐grade squamous intraepithelial lesions, and cervical carcinomas, respectively. Among the 205 HPV‐positive patients, a total of 31 mucosal HPV genotypes were identified of which 16 types, epidemiological classified as high‐risk viruses (HPV16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 66, 68, 73, and 82), have been found in 16.9%, 50.1%, 69.2%, and 78.5% of normal cervix, low‐, and high‐grade cervical squamous intraepithelial lesions, and cervical carcinoma groups, respectively. As expected, the HPV16 was the most represented viral type in all groups examined with frequency rates ranging from 8.7% in normal subjects to 58.5% in invasive carcinoma patients. Ten epidemiologically defined low‐risk HPV types (HPV6, 11, 42, 54, 61, 70, 71, 72, 81, 83) were detected in 2.7%, 7.9%, and 6.1% of normal cervix, low‐, and high‐grade cervical squamous intraepithelial lesions, respectively, and in none of invasive carcinomas. Furthermore, five unknown risk viruses were detected in 3% of low‐grade cervical squamous intraepithelial lesions (HPV30, 32, 67), in 3.1% of high‐grade cervical squamous intraepithelial lesions (HPV62, 90), and in 1.5% of cervical carcinomas (HPV62). Larger epidemiological screening studies, with PCR amplification and followed by either hybridization‐based procedures against sequence targets of all known HPV types or sequence analysis studies, are needed in order to assess the epidemiological risk of less represented HPV types, to identify unknown viruses, and to monitor the future eventual spread of unusual viral types related to vaccination programs and/or population mobility. J. Med. Virol. 78:1663–1672, 2006. © 2006 Wiley‐Liss, Inc.